К экспериментальному определению эффективности пластинчатых каплеуловителей теплообменников контактного типа - Боровок, С. В.; Братута, Эдуард Георгиевич; Круглякова, Ольга Владимировна (НТУ "ХПИ", 2012)
The description of the test desk and new procedure of research of a lamellar type separator of contact heat and mass exchanger, as well as the generalized experimental data in the form of dependence of hydraulic resistance and effectiveness ratio of separation in function of regime-geometrical characteristics of this process is resulted.
Keywords: энергосбережение; энергоносители; охлаждение воды; каплеуловители; капельная влага; энергозатраты; газокапельный поток; весовой метод; гидравлическое сопротивление